Dietary shifts influenced by livestock grazing shape the gut microbiota composition and co‐occurrence networks in a local rodent species. Issue 2 (30th November 2018) - Li, Guoliang; Li, Jing; Kohl, Kevin D.; Yin, Baofa; Wei, Wanhong; Wan, Xinrong; Zhu, Baoli; Zhang, Zhibin
Abstract: The collapse of large wild herbivores with replacement of livestock is causing global plant community and diversity shifts, resulting in altered food availability and diet composition of other sympatric small herbivores in grasslands. How diet shifts affect the gut microbiota of small mammals and whether these changes may translate into complex interactions among coexisting herbivores remain largely unknown. We conducted both a field experiment and a laboratory diet manipulation experiment to test whether sheep grazing induces a diet shift and thus alters the gut microbiota of a small rodent species living in grassland. We found that enclosures subjected to grazing were mostly dominated by Stipa krylovii (accounting for 53.6% of the total biomass) and that voles consumed significantly more S. krylovii and less Cleistogenes squarrosa in grazed enclosures. Voles in grazing enclosures exhibited significantly lower abundances of Firmicutes, higher abundances of Bacteroidetes and significantly lower measurements of alpha diversity. The microbiota from voles in the grazed enclosures had a smaller and more simplified co‐occurrence network with relatively higher percentage of positive interactions. Analysis based on dietary clusters indicated that grazing‐induced changes in diet composition contributed to the distinct gut microbial community of voles in enclosures. We verified our findings using laboratory experiments, in which voles were exclusively fed C. squarrosa (high carbohydrate, high fibre and high in secondary compounds), S. krylovii (low carbohydrate, low fibre and low in secondary compounds) or Leymus chinensis (nutritionally intermediate). We observed that the gut microbiota of voles changed with the three different diets, supporting the idea that the effects of sheep grazing on the gut microbiota of Brandt's voles may be related to grazing‐induced diet shifts. Our results highlighted the negative effects of livestock grazing on small mammals in grassland via changes in plant community and gut microbiota of small mammals and help to better understand the cascading consequences of realistic scenarios of world‐wide decline in large wild herbivores. Abstract : The authors' study provides an effective example of how the replacement of wildlife by livestock cascades to affect the coexisting small mammals. This work also explicitly highlights that gut microbes may modulate the population responses of small mammals to livestock.